2021
DOI: 10.2991/assehr.k.210427.033
|View full text |Cite
|
Sign up to set email alerts
|

Emojis in Indonesian Intergenerational Family WhatsApp Group

Abstract: This study aims to investigate the use of emojis in an Indonesian Intergenerational family WhatsApp group to reveal the types and functions of emojis used in the setting where members from various gender and age groups communicate online. The participants were 26 male and 16 female WhatsApp users aged 21 to 66 years old in the group. The data were collected from five months of interaction in the WhatsApp group. The findings showed that both men and women from various age groups used the following emojis, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…While the most recent studies conducted in Western and Eastern cultures (e.g., Faris et al, 2021;Garda, 2022;Jones et al, 2020;López-Ra, 2021) showed that women now use more emojis than men and do so in different ways, in the current study, gender did not significantly predict emoji frequency and motivation. This result is interesting, as it shows the influence of the Arab culture, with its power distance and avoiding uncertainty characteristics, on both genders.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…While the most recent studies conducted in Western and Eastern cultures (e.g., Faris et al, 2021;Garda, 2022;Jones et al, 2020;López-Ra, 2021) showed that women now use more emojis than men and do so in different ways, in the current study, gender did not significantly predict emoji frequency and motivation. This result is interesting, as it shows the influence of the Arab culture, with its power distance and avoiding uncertainty characteristics, on both genders.…”
Section: Discussioncontrasting
confidence: 82%
“…Emojis and the Effects of the Demographic Variables of the Sender and the Receiver Research on the relationship between gender and emoji usage has produced contradictory findings. Recent research (e.g., Faris et al, 2021;Garda, 2022;Jones et al, 2020;López-Rúa, 2021) has shown that women use more emojis than men, which matches the common knowledge that states that women experience and exhibit emotions more than men. In contrast, an earlier study by Tossell et al (2012) found that men use a more diverse range of emojis than women, and the studies of An et al (2018) and Aretz and Mierke (2019) showed that gender has no effect on emoji usage.…”
Section: Emoji As a Social Presence Toolmentioning
confidence: 56%